MENUMBUHKAN SIKAP DISIPLIN MELALUI PEMBUATAN ATURAN KELAS DENGAN STRATEGI PENGELOLAAN KELAS YANG EFEKTIF - Firsly Sekarrini; Yunita Andriyani; Tin Rustini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
In this research article, the author will focus on discipline first and then continue to explain why it is important to have discipline and this can be achieved by having classroom rules and effective classroom management. The term "discipline" is applied to penalties that are a consequence of breaking the rules. The purpose of discipline is to set boundaries that limit certain behaviors or attitudes that are considered harmful or contrary to school policies, educational norms, school traditions, etc. As for the discussion of this article, it also discusses several theories that are used as a reference source in making this scientific article such as the theory of Positive Approach, Teacher effectiveness training, Adlerian approaches, and appropriate school learning theory which will be discussed for determination and in-depth research on classroom management strategies. which can be considered effective. Then also discussed about the purpose of classroom management so as to create a disciplined environment, which of course will play an important role in creating a conducive environment for learning.